Routes of Vitamin B12 Supplementation: Clinical Evidence, Limitations, and Practical Considerations - Alina Semianiuk; Małgorzata Stopa; Ewa Szczęsna; Paweł Drymluch; Wiktoria Lewicka; Konrad Szaliński; Izabella Sośniak; Adrianna Moreń (Quality in Sport)
Introduction and purpose Vitamin B12 deficiency remains an underdiagnosed condition with significant hematological, neurological, and psychiatric consequences. The aim of this review is to evaluate and compare the efficacy, indications, and clinical applicability of oral, sublingual, intramuscular, and subcutaneous vitamin B12 supplementation routes, and to provide evidence-based recommendations tailored to patient-specific conditions.